Key techniques of cognitive convergence networks - Chun-gang YANG; Jian YUE; Jian-dong LI; Min SHENG; Hong-yan LI; Qin LIU (Tongxin xuebao)
Concentrating on the development of heterogeneous cellular networks and cognitive radio networks, the cogni-tive cellular networks, femtocell and WiFi 2.0 networks were firstly summarized, respectively. The promising combina-tion potentials of them motivates to define the newly-form networking architecture termed as the cognitive convergence network. In addition, two cognition loops of cognitive resource management and cognitive interference management were proposed to mitigate the intra-tier and inter-tier interference. These cognition loops can help to improve the end-to-end quality of user experience. Finally, the future development and the key techniques of the presented the cognitive conver-gence networks was looked forward.